2004
DOI: 10.1002/acp.1086
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effort during note taking

Abstract: Note taking is a complex activity that requires comprehension and selection of information and written production processes. Here we review the functions, abbreviation procedures, strategies, and working memory constraints of note taking with the aim of improving theoretical and practical understanding of the activity. The time urgency of selecting key points and recording them while comprehending new information at the same time places significant demands on the central executive and other components of worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
273
1
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 389 publications
(289 citation statements)
references
References 91 publications
6
273
1
9
Order By: Relevance
“…This is confirmed by Piolat et al (2004) and Bui et al (2013), who state that the process of note-taking is cognitively demanding. University students, and first-year students in particular, have been battling with the question of how to capture and recall the flow of information in traditional lecture periods for many years (Piolat et al 2004).…”
Section: The Value Of Note-taking As a Learning Activitysupporting
confidence: 53%
See 2 more Smart Citations
“…This is confirmed by Piolat et al (2004) and Bui et al (2013), who state that the process of note-taking is cognitively demanding. University students, and first-year students in particular, have been battling with the question of how to capture and recall the flow of information in traditional lecture periods for many years (Piolat et al 2004).…”
Section: The Value Of Note-taking As a Learning Activitysupporting
confidence: 53%
“…This is confirmed by Piolat et al (2004) and Bui et al (2013), who state that the process of note-taking is cognitively demanding. University students, and first-year students in particular, have been battling with the question of how to capture and recall the flow of information in traditional lecture periods for many years (Piolat et al 2004). This may be because students who take notes need to pay attention, organise the information, and then record it in an understandable manner before it is forgotten (Bui and Myerson 2014).…”
Section: The Value Of Note-taking As a Learning Activitysupporting
confidence: 53%
See 1 more Smart Citation
“…It has been stipulated that the production of notes places high demands on the central executive functions as it concurrently involves comprehension, selection, and production processes. Additionally, it has been shown that 'note-taking' requires less executive mobilization than writing and that when note-taking is based on a text, the length of that text is positively correlated with cognitive effort (Piolat et al, 2005). One possible explanation for these findings could be that the amount of information concurrently being processed in the LT-WM is what defines the cognitive demands.…”
Section: Complex Cognitionmentioning
confidence: 80%
“…During 'note-taking', for instance, the object is condensation rather than elaboration. Notetaking refers to the production of short paragraphs of text containing, for instance, a shopping list or the minutes of a work meeting (Piolat, Olive, & Kellogg, 2005). It has been stipulated that the production of notes places high demands on the central executive functions as it concurrently involves comprehension, selection, and production processes.…”
Section: Complex Cognitionmentioning
confidence: 99%